Bromate reduction by Shewanella species depends on both endogenous and exogenous iron - Takahashi, Natsuki; Fujiya, Hiroko; Sato, Haruhiko; Yamamura, Shigeki; Amachi, Seigo (Frontiers in Microbiology, 2026)
In this study, we isolated Shewanella sp. strain M-Br, a bromate (BrO3−)-reducing bacterium, from seawater. In the presence of lactate as the electron donor, this strain reduced 250 μM bromate to bromide (Br−) in 3 days. Interestingly, bromate reduction by M-Br was ferric iron [Fe(III)]-dependent, and its bromate reduction rate was proportional to the Fe(III) concentration in the medium. Subsequently, a washed cell suspension of M-Br was prepared to determine whether the effect of Fe(III) on bromate reduction by M-Br is due to the endogenous iron sources, such as c-type cytochromes, or exogenous iron sources, such as redox mediators. Notably, cells pre-grown in the absence of Fe(III) did not reduce bromate, regardless of the addition of exogenous Fe(III). In contrast, cells pre-grown with Fe(III) reduced bromate upon the addition of exogenous Fe(III) to the cell suspension. Such iron-dependent bromate reduction was also observed in other Shewanella species, such as S. putrefaciens CN-32 and S. oneidensis MR-1. Our results suggest that both endogenous and exogenous iron are essential for bromate reduction by Shewanella species. Based on these results, we proposed a model, in which outer membrane multi-heme cytochromes, such as MtrC and OmcA, reduce Fe(III) to Fe(II), which further chemically reduces bromate to bromide. Such bacteria are useful for the removal of bromate, a potential human carcinogen, from drinking water.